Ringu - Takahashi, Hiroshi; Kawai, Shin'ya.; Ichise, Takashige; Sento, Takenori; Nakata, Hideo; Matsushima, Nanako; Nakatani, Miki.; Sanada, Hiroyuki; 1924-2006.; Hiih.; Kawai, Kenji; Takahashi, Nobuyuki; et al. (Universal City, CA : DreamWorks Home Entertainment, 2003)
"A mysterious video has been linked to a number of deaths, and when an inquisitive journalist finds the tape and views it herself, she sets in motion a chain of events that puts her own life in danger"--Container.
DVD all region.
Japanese language with English subtitles.
Nanako Matsushima, Miki Nakatani, Hiroyuki Sanada, Yuko Takeuchi, Hitomi Sato, Yoichi Numata.
Original songs by Hiih ; original score by Kenji Kawai ; edited by Nobuyuki Takahashi ; cinematography by Junichiro Hayashi.
Based on the novel "The Ring" by Koji Suzuki.
"The original movie that inspired "The Ring"--Container.
Keywords: Death -- Drama; Murder -- Drama; Feature films; Foreign films; Horror films